Exploring faculty perceptions towards electronic health records for nursing education. (31st October 2014) - Kowitlawakul, Y.; Chan, S.W.C.; Wang, L.; Wang, W.
Abstract : Background: The use of electronic health records in nursing education is rapidly increasing worldwide. The successful implementation of electronic health records for nursing education software program relies on students as well as nursing faculty members. Aims: This study aimed to explore the experiences and perceptions of nursing faculty members using electronic health records for nursing education software program, and to identify the influential factors for successful implementation of this technology. Methods: This exploratory qualitative study was conducted using in‐depth individual interviews at a university in Singapore. Seven faculty members participated in the study. The data were gathered and analysed at the end of the semester in the 2012/2013 academic year. Results: The participants' perceptions of the software program were organized into three main categories: innovation, transition and integration. The participants perceived this technology as innovative, with both values and challenges for the users. In addition, using the new software program was perceived as transitional process. The integration of this technology required time from faculty members and students, as well as support from administrators. Limitations: The software program had only been implemented for 2–3 months at the time of the interviews. Consequently, the participants might have lacked the necessary skill and competence and confidence to implement it successfully. In addition, the unequal exposure to the software program might have had an impact on participants' perceptions. Conclusion: The findings show that the integration of electronic health records into nursing education curricula is dependent on the faculty members' experiences with the new technology, as well as their perceptions of it. Hence, cultivating a positive attitude towards the use of new technologies is important. Implications for nursing and health policy: Electronic health records are significant applications of health information technology. Health informatics competency should be included as a required competency component in faculty professional development policy and programmes.